Psychometric Properties in a Pilot Predisposition to Bullying Test (PBT) for Children Aged 7 to 9 Years - Choy, Rosana (2016)
The purpose of this study is to determine the psychometric properties of a pilot Predisposition to Bullying Test (PBT) in children aged between 7 and 9 years. Utilizing a cross-sectional method, we developed a graphic evaluation instrument which was applied to 91 intentionally selected children. The instrument fit approached the level conventionally recognized as adequate. The results show that the instrument has adequate validity and reliability.